Species-level microbiota of ticks and fleas from Marmota himalayana in the Qinghai-Tibet Plateau - Dong, Lingzhi; Li, Yaben; Yang, Caixin; Gong, Jian; Zhu, Wentao; Huang, Yuyuan; Kong, Mimi; Zhao, Lijun; Wang, Feifei; Lu, Shan; Pu, Ji; Yang, Jing (Frontiers in Microbiology, 2023)
Introduction Ticks and fleas, as blood-sucking arthropods, carry and transmit various zoonotic diseases. In the natural plague foci of China, monitoring of Yersinia pestis has been continuously conducted in Marmota himalayana and other host animals, whereas other pathogens carried by vectors are rarely concerned in the Qinghai-Tibet Plateau. Methods In this study, we investigated the microbiota of ticks and fleas sampling from M. himalayana in the Qinghai-Tibet Plateau, China by metataxonomics combined with metagenomic methods. Results By metataxonomic approach based on full-length 16S rDNA amplicon sequencing and operational phylogenetic unit (OPU) analyses, we described the microbiota community of ticks and fleas at the species level, annotated 1,250 OPUs in ticks, including 556 known species and 492 potentially new species, accounting for 48.50% and 41.71% of the total reads in ticks, respectively. A total of 689 OPUs were detected in fleas, consisting of 277 known species (40.62% of the total reads in fleas) and 294 potentially new species (56.88%). At the dominant species categories, we detected the Anaplasma phagocytophilum (OPU 421) and potentially pathogenic new species of Wolbachia, Ehrlichia, Rickettsia, and Bartonella. Using shotgun sequencing, we obtained 10 metagenomic assembled genomes (MAGs) from vector samples, including a known species (Providencia heimbachae DFT2), and six new species affliated to four known genera, i.e., Wolbachia, Mumia, Bartonella, and Anaplasma. By the phylogenetic analyses based on full-length 16S rRNA genes and core genes, we identified that ticks harbored pathogenic A. phagocytophilum. Moreover, these potentially pathogenic novel species were more closely related to Ehrlichia muris, Ehrlichia muris subsp. eauclairensis, Bartonella rochalimae, and Rickettsia limoniae, respectively. The OPU 422 Ehrlichia sp1 was most related to Ehrlichia muris and Ehrlichia muris subsp. eauclairensis. The OPU 230 Bartonella sp1 and Bartonella spp. (DTF8 and DTF9) was clustered with Bartonella rochalimae. The OPU 427 Rickettsia sp1 was clustered with Rickettsia limoniae. Discussion The findings of the study have advanced our understanding of the potential pathogen groups of vectors in marmot (Marmota himalayana) in the Qinghai-Tibet Plateau.